Ivonescimab combined with chemotherapy shows promising efficacy in an ALK fusion-positive lung adenocarcinoma patient with ALK-TKI resistance: a case report - Lin, Meiyuan; Gao, Yuan; Deng, Jun (Frontiers in Oncology, 2025)
This report describes a case of lung adenocarcinoma harboring an echinoderm microtubule-associated protein-like 4–anaplastic lymphoma kinase (EML4–ALK) fusion, high programmed death-ligand 1 (PD-L1) expression, and a Bcl-2-like protein 11 (BIM) deletion polymorphism. The patient was initially treated with alectinib, but experienced rapid disease progression. After repeat genetic testing, therapy was switched to lorlatinib, which again resulted in early progression. Subsequently, treatment with ivonescimab combined with chemotherapy achieved a favorable clinical response. To our knowledge, this is the first reported case of ivonescimab use in such a patient. This case offers a potential reference for the management of ALK fusion–positive lung adenocarcinoma resistant to ALK tyrosine kinase inhibitors (ALK-TKIs).